The Current State of Behavioural Economics Studies : A Bibliometric Analysis - WEI, GAN JIA; Rossazana, Ab Rahim; Abdul Hayy Haziq, Mohamad; Mohd Sabrun, Ibrahim (EconJournals, 2025)
The aim of this paper is to present the current state of the published literature related to behavioural economics studies. This paper presents a bibliometric analysis of 1757 documents on behavioural economics published between 1965 and 2024, using data from Scopus to analyse with tools like Microsoft Excel, BiblioMagika, OpenRefine, and VOSviewer. The findings discover that Kahneman’s (2003) paper, “Maps of Bounded Rationality: Psychology for Behavioural Economics” is the most highly cited document. This paper also identifies five key research clusters: Substance use and behavioural economics, decision-making, behavioural biases, health interventions, and alcohol-related behaviours. James G. Murphy is the most prolific author with 54 publications, while Warren K. Bickel is the most influential with 4018 citations. The United States emerged as the leading contributor with 1012 publications. This paper highlights the significant growth and interdisciplinary nature of behavioural economics, its applications in public health and policymaking, and the need for more research in diverse cultural and regional contexts.